Humanizing the Animal and Animalizing the Human: A Detective Study of Edgar Allan Poe’s The Murders in the Rue Morgue. (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Edgar Allan Poe's The Murders in the Rue Morgue is one of the trilogy, the other two being The Mystery of Marie Roger and The Purloined Letter, that seems to have launched the genre of detective fiction. The story is traditionally read and interpreted as a “locked room” mystery. It is a tale with implicit racial discourses where the orangutan, the criminal animal, reflects the perturbation of white supremacy or the orangutan's murderous aggression exposes the white paranoia and fear of possible violence of the blacks against white sovereignty. But for Jonathan Elmer, the orangutan is a metaphysical being and its distorted, unidentifiable mirror-image represents the irrational animal body of the detective Dupin; it turns out to be Dupin's non-coincident self. Besides, Donna Haraway visualizes the orangutan as belonging to the “border zone” — an in-between state of existence of the humans and the animals — very much like the chimpanzees and gorillas. However, the present research paper aims at exploring the intrinsic human-like qualities of the orangutan as well as the zoomorphical foundation of the non-rational configuration of Dupin — a point which was further scientifically established and consolidated by the Darwinian theory of evolution almost two decades later. Apart from the incessant thrilling suspense that Poe maintains throughout the story, the animalization of the human and the humanization of the animal is what attracts the attention of the readers most. It is also an endeavor to examine and understand the non-human animal psyche and necessarily wipe out the overlapping interspecies binary in the present era of anthropocentrism.